Evaluation of Open Defecation Free Program Policy in Tambak Osowilangun Village Surabaya City - Esa Wahyu Endarti (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study evaluates the implementation of the Open Defecation Free (ODF) Program in Tambak Osowilangun Village, Surabaya City using a qualitative approach with in-depth interviews, documentation, and observation. The findings of the study show that the program has been successful in increasing access to proper sanitation facilities and reducing the incidence of sanitation-related diseases such as diarrhea. Significant challenges still exist, especially related to uneven changes in community behavior and suboptimal maintenance of sanitation facilities. The success of the program is supported by the active involvement of local communities and policy support from local governments, but is hampered by factors such as limited infrastructure in remote areas and cultural resistance to changes in sanitation practices. The limitations of this study include geographic coverage limited to a single village and a qualitative approach that may not cover the variation of experiences across the regions affected by the ODF program.